Information systems : the key to evidence-based health practice - Rodrigues, Roberto J. (2000)
Discusses the role of information in evidence-based practice (EBP) together with questions of how advanced information systems and technology (IS&T) can contribute to the establishment of a broader perspective for EBP. Examines the development, validation and use of a variety of sources of evidence and knowledge that go beyond the well-established paradigm of research, clinical trials and systematic literature review. Focuses on opportunities and challenges in the implementation and use of IS&T and knowledge management tools for six application areas viz. reference databases, contextual data, clinical data respositories, administrative data repositories, decision support software, and internet-based interactive health information and communication.